Comparative Histomorphological and Histochemical Studies on the Oesophagus of Nile Tilapia Oreochromis niloticus and African Catfish Clarias gariepinus. (10th November 2014) - Awaad, Ashraf Sayed; Moawad, Usama Kamal; Tawfiek, Mohamed Gomaa
Abstract : The present work aimed to describe and compare both gross and microscopic structure of the oesophagus of Nile tilapia ( Oreochromis niloticus ) and African catfish ( Clarias gariepinus ). For this purpose, 60 specimens of oesophagus of Nile tilapia (omnivorous fish) and African catfish (carnivorous fish) were collected and processed. Anatomically, the oesophagus of both species appeared as a short tube with longitudinal mucosal folds. Using scanning electron microscope, the epithelial surface of the esophagus showed primary and secondary mucosal folds in both species while tertiary folds were observed in that of tilapia only. Histologically, the oesophagus consisted of four distinct layers: mucosa, submucosa, muscularis, and serosa. The oesophageal mucosa consisted of stratified epithelium with few mucous secreting cells in catfish and many mucous secreting cells in tilapia. Two types of mucous secreting cells reacted positively with both periodic acid shiff (PAS) and alcian blue (AB); rounded and elongated cells that were recognized in the esophageal epithelium of tilapia and only elongated oval cells were observed in that of catfish. In conclusion, the obtained histomorphological differences in esophagus of both fish species may be attributed to their different feeding habits and type of food.